Effect of Financial Attitudes, Financial Knowledge, Locus of Control, and Financial Self-Efficacy to Financial Management Behavior in Millennial Generation - Ervina Lukesi; Erna Retna Rahadjeng; Novita Ratna Satiti (Jurnal Manajemen Bisnis dan Kewirausahaan (JAMANIKA), 2021)
This research aims to review the influence of financial attitude, financial knowledge, mission control, and financial self-efficacy in the millennial generations in Mojolangu. Included in this study as many as 100 respondents purposive sampling method. Sampling technical data to the analysis in this study using multiple linear regression. Based on test results obtained, financial knowledge of financial attitude, locus of control, and financial self-efficacy in partially significant and positive behavior on financial management. The Independent variable most dominant in contributing to the behavior of financial management is the attitude of financial variables.